MODEL PEMBELAJARAN PADA ZAMAN NABI MUHAMMAD SAW - Makbuloh, Deden (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2014)
This paper aims to exsplain the success of ProphetMuhammad SAW, in Islamic education. Social setting at thetime of the Prophet studied as a means to accuratelyunderstand the factors that influence the success. Themethod used is descriptive and historical, data collectionthrough the study of literature. The results show thatIslamic education at the time of the Prophet Muhammadalways current and in line with the real problems and needsthat occur in the Muslim community. Thus, IslamicEducation can be said to be contextual. Modeling Prophetconsistent and enthusiastic friends who maintained is key tosuccess in the ground the Islamic education. With thesuccess of Islamic education in the time of ProphetMuhammad, Muslims can now learn according toperformance Prophet as the key to the success ofdeveloping the progress of human civilization